Hulk (2008), volume 2 ebook Red & green. - Loeb, Jeph (Hulk (2008), 2011)
Collects Hulk (2008) #7-9 & King-Size Hulk #1 While Bruce Banner discovers the unbridled carnage a pack of Wendigos can unleash, She-Hulks arms herself with an arsenal of advanced S.H.I.E.L.D. weaponry and itching for payback, unites the Lady Liberators with one goal: subdue the Red Hulk, and make him pay in the process. Author: Jeph Loeb. Illustrator: Arthur Adams. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com